Influence of Different Lithium Compounds on Hydration and Mechanical Properties of Calcium Sulfoaluminate Cement - Deng, Hongyang (Materials (Basel), 2020)
This work investigated the influence of three different lithium compounds, lithium carbonate (Li(2)CO(3)), lithium sulfate (Li(2)SO(4)) and lithium chloride (LiCl), on the hydration and mechanical properties of calcium sulfoaluminate (CSA) cement mixtures. Five concentrations of Li(+), 0, 0.05, 0.11, 0.16 and 0.22 mmol/g of cement, were chosen, and then the proportions (by mass) of three lithium compounds were determined. Compressive strengths at 8 h, 24 h and 28 days were tested. Meanwhile, an early hydration heat test, thermogravimetric (TG) analysis, X-ray diffraction (XRD) and scanning electron microscope (SEM) techniques were performed to study the influences of different lithium compounds on properties of CSA cement mixtures. The experimental results show that three lithium compounds can all accelerate the early hydration process of CSA cement. There is not a remarkable difference on the properties of CSA cement pastes with a different content of Li(+). The anion of lithium compounds can also affect the properties of CSA cement pastes, the accelerating effects of LiCl and Li(2)SO(4) are more significant than that of Li(2)CO(3), but there is not a distinct difference between LiCl and Li(2)SO(4).